Application of Hydrothermal Treatment to High Concentrated Sewage Sludge for Anaerobic Digestion Process - Orikawa, M.; Kamahara, H.; Atsuta, Y.; Daimon, H. (International Journal of Renewable Energy Development, 2013)
Tomato and seaweed were produced by utilizing CO2 and heat discharged from power generation using biogas in Toyogawa biomass park, Japan. The biogas was obtained by anaerobic digestion with hydrothermal treatment. The hydrothermal treatment was applied to the high concentrated sewage sludge (22 % total solids (TS) dewatered sludge). The purpose of this study is to clarify the effect of hydrothermal treatment on the qualities of high concentrated sewage sludge, by analyzing particulate organic carbon (POC) and dissolved organic carbon (DOC). The hydrothermal treatment was investigated under 10-60 min of treatment time, 180-200 Â°C of temperature, 10-22 %-TS of sewage sludge concentration. The results showed that the DOC in each conditions increased through hydrothermal treatment. The highest DOC obtained was 67 % of total carbon concentration, when the temperature was 180 Â°C, treatment time was 60 min and sewage sludge concentration was 10 %-TS. Furthermore, the viscosity of treated sewage sludge was decreased by hydrothermal treatment. In batch anaerobic digestion test, methane gas production was confirmed. In addition, this study evaluated the energy balance of this system. Thus, the results of this study indicated that the possibility of application of hydrothermal treatment to high concentrated sewage sludge for anaerobic digestion process.Â